Ethical dimensions of neglected tropical disease programming. (18th December 2020) - Addiss, David G; Kienast, Yvonne; Lavery, James V
Abstract: The global movement to control and eliminate neglected tropical diseases (NTDs) is grounded in an ethic of social justice, solidarity and health equity. NTD programmes deliver significant health benefits in socially complex environments characterized by poverty and economic disparity. We used two ethics frameworks—principlism and Upshur's public health framework—to examine ethical challenges faced by NTD programmes. They include management of serious adverse reactions associated with preventive chemotherapy, centralization of decision-making, 'opt-out' policies for school-based deworming, incomplete evidence for 'pro-poor' impact and persistent inequities in global partnerships. NTD programmes must actively address ethical challenges while pursuing global health goals.